Implementation and Application of Functional Languages 23rd International Symposium, IFL 2011, Lawrence, KS, USA, October 3-5, 2011, Revised Selected Papers - Gill, Andy; Hage, Jurriaan (Theoretical Computer Science and General Issues, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 23rd International Symposium on Implementation and Application of Functional Languages, IFL 2011, held in Lawrence, Kansas, USA, in October 2011. The 11 revised full papers presented were carefully reviewed and selected from 33 submissions. The papers by researchers and practitioners who are actively engaged in the implementation and the use of functional and function based programming languages describe practical and theoretical work as well as applications and tools. They discuss new ideas and concepts, as well as work in progress and results.